Where to from here? A quality improvement project investigating burns treatment and rehabilitation practices in India - Jagnoor, J. (BMC Res Notes, 2018)
OBJECTIVE: To describe the capacity of the Indian healthcare system in providing appropriate and effective burns treatment and rehabilitation services. RESULTS: Health professionals involved in burns treatment or rehabilitation at seven hospitals from four states in India were invited to participate in consultative meetings. Existing treatment and rehabilitation strategies, barriers and enablers to patient flow across the continuum of care and details on inpatient and outpatient rehabilitation were discussed during the meetings. Seventeen health professionals from various clinical backgrounds were involved in the consultation process. Key themes highlighted (a) a lack of awareness on burn first aid at the community level, (b) a lack of human resource to treat burn injuries in hospital settings, (c) a gap in burn care training for medical staff, (d) poor hospital infrastructure and (e) a variation in treatment practices and rehabilitation services available between hospitals. A number of opportunities exist to improve burns treatment and rehabilitation in India. Improvements would most effectively be achieved through promoting multidisciplinary care across a number of facilities and service providers. Further research is required to develop context-specific burn care models, determining how these can be integrated into the Indian healthcare system.